Modeling and analysis of electromagnetic interference radiation for broadband power line communication networks - Pang, Teng Seng (2011)
Power Line Communications (PLC) is a term used to identify technologies, equipment, applications, and services aiming at providing users with communication means over the existing power lines. With the increasing demands for broadband access and home networking, new technologies are being created to tap into this growing broadband communication market. Among them, PLC technology has recently attracted lots of attention worldwide due to its convenience of wide availability and advantage of low cost. However, like all other technologies, PLC also faces its own set of obstacles and technical challenges. The power line is designed to transmit electrical power at low frequency, and it appears as a harsh environment for the high frequency communication signals. Electromagnetic interference (EMI) radiation from PLC networks is a major concern for the widespread use of broadband PLC technology. As the power line is not shielded, it behaves like an antenna causing high radiation when high frequency PLC signals are transmitted.